Labour and the Waffle: Unions Confront Canadian Left Nationalism in the New Democratic Party - Blocker, David (Labour / Le Travail, 2021)
In the late 1960s and early 1970s, the Waffle movement in the New Democratic Party (ndp) emerged as a leading proponent of Canadian left economic nationalism. The Waffle, which formed around the “Manifesto for an Independent and Socialist Canada” and challenged the leadership of the ndp from 1969 to 1973, represents a dynamic convergence of many of the social movements that comprised the New Left in Canada. This article examines the evolution of the Waffle’s position on international unionism alongside the reaction of pro-ndp labour leaders to this New Left incursion into the party. ndp-allied labour leaders expressed suspicion and concern for the group’s agenda almost from its inception. The Waffle’s success in appealing to younger and nationalist-minded members of international unions turned suspicion into active opposition. As polarization within the ndp increased, workers’ support for the Waffle within the Canadian labour movement led moderate union leaders to conclude the group must be expunged from the Ontario ndp. Ironically, after the Waffle’s departure from the party the group largely repudiated nationalist breakaways from international unions while, in the ensuing decades, the mainstream labour movement embraced Canadian nationalism.